Efficient separation of oily wastewater using polyethersulfone mixed matrix membrane incorporated with halloysite nanotube-hydrous ferric oxide nanoparticle - Wan Ikhsan, Syarifah Nazirah; Yusof, Norhaniza; Aziz, Farhana; Misdan, Nurasyikin; Ismail, Ahmad Fauzi; Lau, Woei-Jye; Jaafar, Juhana; Wan Salleh, Wan Norharyati; Hairom, Nur Hanis Hayati (Elsevier, 2018)
In this work, self-synthesized halloysite nanotube-hydrous ferric dioxide (HNT-HFO) nanocomposites prepared via chemical precipitation method were incorporated in polyethersulfone (PES) to fabricate novel ultrafiltration (UF) mixed matrix membranes (MMMs) for oil-water separation process. Prior to filtration experiments, the morphologies and physicochemical properties of prepared HNT-HFO nanocomposites and MMMs were characterized using scanning electron microscope with energy-dispersive X-ray, transmission electron microscope, Fourier-transform Infrared spectroscope, atomic force microscope and contact angle goniometer. It was found that the membrane contact angle decreased remarkably from 81.39° to about 50.30° upon addition of 23.08 wt% of HNT-HFO nanocomposite (2.0 loading ratio) in the PES matrix. The improved surface hydrophilicity resulted in the flux enhancement in the MMM, achieving close to 650 L/m2 h bar of pure water flux. This value was about 10 times higher than the flux shown by the pristine PES membrane. In addition to the excellent water flux, the MMM also exhibited almost complete elimination of oil molecules (99.7% rejection) when tested with 1000 ppm oily solution. The findings indicated the potential use of the newly developed MMMs for efficient purification of oily wastewater in the oil field and refinery processes.